Determinants of Credit Decision Making by Micro Enterprises in Surabaya - Muhammad Firdaus Nur Ananda; Shochrul Rohmatul Ajija (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
This study aims to see how financial literacy factors and business cycle conditions and other variables affect the decision of micro-entrepreneurs in Surabaya to apply for credit. In total of 450 micro-entrepreneurs in Surabaya were sampled in this study. Retrieval of data using the Non-Probability Sampling method, which is a sampling technique in which all members of the population do not have the same opportunity to become research samples. Based on the results of the analysis, it shows that together all independent variables have an influence on the dependent variable, the credit decision. Furthermore, business cycle conditions, collateral ownership, and government policies have a positive and partially significant effect on credit decisions.